2023
DOI: 10.1002/acr2.11535
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Biomarkers for Rheumatoid Arthritis–Associated Interstitial Lung Disease: A Systematic Review

Abstract: Background Biomarkers have been proposed as tools to aid in the identification and prognostication of interstitial lung disease (ILD) in rheumatoid arthritis (RA). We performed a systematic review of studies evaluating peripheral blood biomarkers and their association with RA‐ILD and its prognosis. Methods Medline, Embase, the Cochrane Library, and Scopus were queried for relevant studies, with the final search update on July 12, 2021. We included studies evaluating per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…The MUC5B promoter variant is the strongest genetic risk factor for usual interstitial pneumonia (UIP), the prototypic fibrotic RA‐ILD subtype 9,10 . Peripheral blood biomarkers have been shown to predict RA‐ILD 11–13 . Establishing biomarkers of pulmonary damage may be particularly helpful in identifying preclinical RA‐ILD, even before changes in PFTs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The MUC5B promoter variant is the strongest genetic risk factor for usual interstitial pneumonia (UIP), the prototypic fibrotic RA‐ILD subtype 9,10 . Peripheral blood biomarkers have been shown to predict RA‐ILD 11–13 . Establishing biomarkers of pulmonary damage may be particularly helpful in identifying preclinical RA‐ILD, even before changes in PFTs.…”
Section: Figurementioning
confidence: 99%
“…9,10 Peripheral blood biomarkers have been shown to predict RA-ILD. [11][12][13] Establishing biomarkers of pulmonary damage may be particularly helpful in identifying preclinical RA-ILD, even before changes in PFTs. Matrix metalloproteinases (MMPs) are responsible for regulation and degradation of the extracellular matrix and have been associated with RA-ILD previously, 14 so they may be a…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] In addition to autoantibodies and select genetic variants already mentioned, other categories of candidate biomarkers evaluated in RA-ILD to date have included extracellular matrix proteins, cytokines and chemokines, lung epithelial-related proteins, tumor markers, and growth factors. 8 Because these risk factors are not sufficient for clinical use to detect RA-ILD, 9 the discovery of novel biomarkers that can help stratify patients at risk for or with undiagnosed RA-ILD is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and epidemiologic studies have identified older age, male sex, cigarette smoking, higher RA disease activity, RA autoantibodies, and genetic risk alleles, including the gain‐of‐function MUC5B rs35705950 promoter variant, as risk factors for RA‐ILD 5–7 . In addition to autoantibodies and select genetic variants already mentioned, other categories of candidate biomarkers evaluated in RA‐ILD to date have included extracellular matrix proteins, cytokines and chemokines, lung epithelial–related proteins, tumor markers, and growth factors 8 . Because these risk factors are not sufficient for clinical use to detect RA‐ILD, 9 the discovery of novel biomarkers that can help stratify patients at risk for or with undiagnosed RA‐ILD is needed.…”
Section: Introductionmentioning
confidence: 99%